Gona - Semaw, Sileshi; Rogers, Michael J. (The International Encyclopedia of Biological Anthropology, 2018)
Keywords: dept.ant

The first technical sequences in human evolution from East Gona, Afar region, Ethiopia - de Lumley, Henry; Barsky, Deborah; Moncel, Marie Hélène; Carbonell, Eudald; Cauche, Dominique; Celiberti, Vincenzo; Notter, Olivier; Pleurdeau, David; Hong, Mi-Young; Rogers, Michael J.; Semaw, Sileshi (Antiquity, 2018)
Gona in the Afar region of Ethiopia has yielded the earliest Oldowan stone tools in the world. Artefacts from the East Gona (EG) 10 site date back 2.6 million years. Analysis of the lithic assemblage from EG 10 reveals the earliest-known evidence for refitting and conjoining stone artefacts. This new information supplements data from other Oldowan sites in East Africa, and provides an important insight into the technological capacities and evolutionary development of hominins during this period.
Keywords: East Gona; Ethiopia; Oldowan; dept.ant; knapping; peer-reviewed; refitting

The Early Acheulean ~1.6–1.2 Ma from Gona, Ethiopia: Issues related to the emergence of the Acheulean in Africa - Semaw, Sileshi; Rogers, Michael J.; Cáceres, Isabel; Stout, Dietrich; Leiss, Amanda C. (The Emergence of the Acheulean in East Africa and Beyond: Contributions in Honor of Jean Chavaillon, 2018)
Konso in Ethiopia and Kokiselei in Kenya, both dated to ~1.7 million years ago (Ma), and FLK West, a recently reported site from Olduvai dated to 1.7 Ma, are the earliest Acheulean sites known in East Africa. Ongoing archaeological investigations at Gona, in the Afar Depression of Ethiopia, have also produced early Acheulean stone assemblages at several sites, estimated to ~1.6–1.2 Ma. A number of sites, including BSN-12 and OGS-12, have yielded archaeological materials comparable to the earliest Konso artifacts. The stone assemblages from the Gona sites consist of crudely made handaxes, cleavers, and picks, as well as Mode I (Oldowan) cores, and débitage. A variety of raw materials were exploited at Gona, with trachyte, rhyolite, and basalt being the most common.Our understanding of the behavioral and ecological background for the emergence of the Acheulean is still limited. Preliminary comparisons of BSN-12 and OGS-12 with other early Acheulean sites demonstrate variability in paleoecological settings as well as raw material use. Current archaeological evidence indicates that early Homo erectus/ergaster use of this new technology was already in place in East Africa ~1.75 Ma. At Gona and elsewhere in Africa, continued survey and excavations are needed to document sites with potential for yielding archaeological traces that will help our understanding of the Oldowan–Acheulean transition, the identity of the toolmakers, and the function of the early Acheulean Large Cutting Tools (LCTs).
Keywords: Ethiopia; Gona; Oldowan–Acheulean transition; Technical behaviors; dept.ant